(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article analyzes the current state and development trends of laboratory diagnostic methods in oncology based on contemporary scientific literature. Within the framework of a literature review, the diagnostic and prognostic significance of biochemical laboratory parameters, tumor markers, immunological, and molecular genetic diagnostic methods used in the diagnosis of oncological diseases is discussed.